(3GdfLjHjGJs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3efUhQ GdMGhi GdYdhi GdNLfOi s)
(3ChdgG (B:s
(3bGd GdaGVd Gdehd GdSeQbfOi ai GdbSe GdChd ef fLjHjGJg , GdehShe HGdCSHGH hGdYdGeGJ (B: (3GdUOGY Cde ai CYVGA GdQCS s
(3BNQgG (B:s
(3Ke HeGA MeGV GdCJQL , Ke HeGA GdBS GdCNVQ eQJjf , hjfYe SMbg hjSJYed s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B195 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH (B1) s
Keywords: (3GdWHs